(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
This research aims to study the effect of rectangular slots on the pressure distribution in an inclined slider bearing. The pressure gradient in a one-dimensional fluid sheet was theoretically calculated using Reynolds’ equation. The practical results were compared by the tilted sliding bearing, where the researcher manufactured and developed the device by adding pressure sensors along the pads. Four pads with varied slot widths (3, 5, and 8mm) and a depth of 2mm were created: one without grooves and three with rectangular grooves. The research examined various factors, including sliding velocities, pad inclination values, and oil temperatures. The conclusions indicate that the flat model’s pressure distribution was significantly superior to the slot models by percentages of 0.5%, 4.2%, and 14%, respectively. One significant conclusion for models with slots was that as the inclination increases, the maximum hydrodynamic pressure began to move towards the pad’s beginning. Thus, grooved versions can be employed in applications needing less load and weight. Experimental comparisons between the present and previous work have been made (just in behaviors). The comparison sample was flat; the results indicated that sensors produced higher pressure levels than manometer tubes under the same operating conditions.